Design and analysis of aircraft structures to reinforce passenger to freighter conversion - Babin Vivek Baskaran (2017)
Passenger-to-Freighter (P2F) conversion provides a highly economical solution to airfreight providers. Airbus forecasts a demand for more than 600 narrow bodies to be converted to freighters over the next 20 years. This dissertation mainly discusses about the structural modifications of A320/A321 aircraft, in order to meet the design objectives and regulatory requirements. The P2F conversion process involves extensive modifications including strengthening of the fuselage monocoque structure, installation of a new cargo door and surround structure etc. The structures on the aircraft will have to be reinforced to take on the cargo loads. The structures of the passenger aircraft are analysed using finite elements modelling technique, to determine the structural strength and reinforcements to carry the applied cargo loads. The CAD modelling of the structure is performed using software called CATIA V5. During the design, the aircraft's weight and centre of gravity are also ensured not to exceed the original envelopes. The work presented in this dissertation is still at its infant stage and will probably need further study before implementation.